Influence of Market Rate of Return (Rm) and Systematic Risk (?) on Stock Decision Making in Non-State-Owned Banks (2019–2023) - Hayyu Fadli Firmadhani,; Wiwiek Kusumaning Asmoro,; Atik Tri Andari,; Athoillah, Ahmad Saifi (JBS Nexus, 2025)
This study investigates the influence of the Market Rate of Return (Rm) and Systematic Risk (?) on stock investment decision-making in non-state-owned banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Employing a quantitative approach with a causal–associative research design, the study uses secondary data and applies multiple linear regression analysis. The empirical findings reveal that both the Market Rate of Return (Rm) and Systematic Risk (?) have no significant partial effect on stock investment decisions. Moreover, the two variables jointly also do not demonstrate a significant influence. These results indicate that investors may rely on other determinants beyond CAPM variables when making investment decisions in the non-state-owned banking sector. The study suggests that companies enhance performance stability through risk diversification and improved transparency to strengthen investor confidence. Furthermore, managers are encouraged to emphasize non-financial value drivers, such as innovation capability, digital transformation, and financial literacy enhancement, to support more informed investment decision-making.